Unicorn Diaries : Welcome to Sparklegrove - Book 8 - Elliott, Rebecca (New York : Scholastic, Inc., 2023)
Bo Tinseltail and friends welcome a jackalope family to Sparklegrove Forest, and when they learn the family is being chased by centaurs everyone bands together to help the jackalopes live in peace.
Keywords: Unicorns -- Juvenile fiction; Mythical animals -- Juvenile fiction; Bullies and bullying -- Juvenile fiction; Helpfulness -- Juvenile fiction; Diaries -- Juvenile fiction; Unicorns -- Fiction; Mythical animals -- Fiction; Bullies and bullying -- Fiction; Helpfulness -- Fiction; Diaries -- Fiction; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Animals / Dragons, Unicorns & Mythical; Diary fiction